Catholic schools in Kenya: history, achievements and challenges. Issue 2 (3rd July 2019) - Adhiambo, Jacinta Mary
Abstract : The article presents Catholic Schools as an outcome of the partnership that exists between the government of Kenya and the Catholic Church which makes the Church very instrumental in the provision of education in the country. It is in such a context that the historical perspective of the Catholic schools is expounded, highlighting the contribution of Religious Congregations and respective dioceses in the establishment and management of the schools. Further, the article underscores the uniqueness and scope of the Catholic Schools and later enumerates the successes and challenges of Catholic Sponsored Schools. The article makes recommendations and concludes that the Catholic Schools will continue to contribute to improved access to quality and Catholic Education in Kenya as long as the Catholic Church exists.